Molecular Diagnosis of Genital Chlamydia trachomatis Infection by Polymerase Chain Reaction - Khan, ER; Hossain, MA; Paul, SK; Mahmud, MC; Rahman, MM; Alam, MA; Hasan, MM; Mahmud, NU; Nahar, K (Mymensingh Medical Journal, 2011)
Mymensingh Med J. 2011 Jul;20(3):362-365 The abstract of this article is available on the PubMed website